Strong in-plane anisotropy in the electronic structure of fixed-valence β − LuAlB 4 - Reiss, P; Baglo, J; En Tan, H; Chen, X; Friedemann, S; Kuga, K; Grosche, FM; Nakatsuji, S; Sutherland, M (American Physical Society, 2020)
The origin of intrinsic quantum criticality in the heavy-fermion superconductor β-YbAlB4 has been attributed to strong Yb valence fluctuations and its peculiar crystal structure. Here, we assess these contributions individually by studying the isostructural but fixed-valence compound β-LuAlB4. Quantum oscillation measurements and DFT calculations reveal a Fermi surface in βLuAlB4 markedly different from that of β-YbAlB4, consistent with a ‘large‘ Fermi surface in the latter. We also find an unexpected in-plane anisotropy of the electronic structure, in contrast to the isotropic Kondo hybridization in β-YbAlB4.